Agronomic benefits of biochar as a soil amendment after its use as waste water filtration medium. (February 2018) - Werner, Steffen; Kätzl, Korbinian; Wichern, Marc; Buerkert, Andreas; Steiner, Christoph; Marschner, Bernd
Abstract: In many water-scarce countries, waste water is used for irrigation which poses a health risk to farmers and consumers. At the same time, it delivers nutrients to the farming systems. In this study, we tested the hypotheses that biochar can be used as a filter medium for waste water treatment to reduce pathogen loads. At the same time, the biochar is becoming enriched with nutrients and therefore can act as a fertilizer for soil amendment. We used biochar as a filter medium for the filtration of raw waste water and compared the agronomic effects of this "filterchar" (FC) and the untreated biochar (BC) in a greenhouse pot trial on spring wheat biomass production on an acidic sandy soil from Niger. The biochar filter showed the same removal of pathogens as a common sand filter (1.4 log units on average). We did not observe a nutrient accumulation in FC compared to untreated BC. Instead, P, Mg and K were reduced during filtration while N content remained unchanged. Nevertheless, higher biomass ( Triticum L. Spp.) production in BC (+72%) and FC (+37%) treatments (20 t ha −1 ), compared with the unamended control, were found. There were no significant differences in aboveground biomass production between BC and FC. Soil available P content was increased by BC (+106%) and FC (+52%) application. Besides, mineral nitrogen content was reduced in BC treated soil and to a lesser extent when FC was used. This may be explained by reduced sorption affinity for mineral nitrogen compounds on FC surfaces. Although the nutrients provided by FC decreased, due to leaching in the filter, it still yielded higher biomass than the unamended control. Graphical abstract: Image 1 Highlights: Biochar as a filter material efficiently reduces pathogen loads from waste water. Biochar is depleted in P, K and Mg during filtration. Biochar and filterchar increased biomass production by up to 72%, which is attributed to a direct P fertilization effect.